Family variables associated with suicidal behaviors: a review of literature - Gil Díaz, Morelia Erandeni (Consorcio de Universidades Mexicanas A.C., 2019)
The World Health Organization (2014) considers suicide a complex and multicausal phenomenon. As such, this phenomenon cannot be explained by only one variable and its presence or development in an individual is likely be due to multiple factors of diverse origins. According to data reported by the Panamerican Health Organization (2016), children and adolescents are the groups most at risk for suicidal attempts. The present study is a review of exploratory literature on variables related to the family system and the presence of suicidal behaviors. Therefore, the main objective of this literature review was to identify and explore research articles that focused on variables related to the family and suicidal behaviors. The search was carried out during the months of January to May 2019, for which five databases were consulted, considering only research articles that focused on variables regarding family systems and suicidal behaviors. Initially, a total of 60 articles were obtained. According to the inclusion criteria for the literature review, 20 research articles were included in the present inquiry. Through a systematic review of the exploratory literature, several variables regarding family systems and suicidal behaviors were identified, such as family functioning, communication, support received from its members, and others. The absence of these variables is negatively correlated with the presence of suicidal behaviors. Familial variables, specifically those related to interactions between family members, play an important role in the prevention of suicidal behavior.